Intricacies of Radiographic Assessment in Testicular Germ Cell Tumors - Makovník, Marek; Rejleková, Katarína; Uhrin, Ivan; Mego, Michal; Chovanec, Michal (Frontiers in Oncology, 2021)
Testicular germ cell tumors (GCTs) are malignancies with unique biology, pathology, clinical appearance and excellent outcomes. Correct radiographic assessment of GCTs is extremely important for clinical management in several typical scenarios. Advancements in the field of diagnostic medicine brings increasing number of sophisticated imaging methods to increase the performance of imaging studies. Conventional computed tomography (CT) remains the mainstay of diagnostic imaging in the management of GCTs. While certain improvements in sensitivity and specificity are suggested with magnetic resonance (MR) imaging with lymphotrophic nanoparticles in evaluating retroperitoneal lymph nodes during staging procedure, these data need further exploration in larger prospective studies. Common diagnostic dilemma is assessing the post-chemotherapy residual disease in GCTs. Several studies have consistently shown advantages in utility of positron emission tomography (PET) scanning in post-chemotherapy residual disease in retroperitoneum in patients with seminoma, but not with non-seminoma. Recommendations suggest that seminoma patients with residual disease in retroperitoneum larger than 3 cm should be subjected for PET scanning with 18-fluorodeoxyglucose. Relatively high sensitivity, specificity and negative predictive value (80-95%) may guide clinical decision to spare these patients high morbidity of unnecessary surgery. However, positive predictive value of around 50% renders PET scanning difficult to interpret in case of positive finding. These patients often require extremely difficult surgical procedures with high risk of post-operative morbidity. Therefore, seminoma patients with PET positive residual masses larger than 3 cm continue to present serious challenge in decision making of radiologists, oncologists and urologic surgeons. In this article we aim to summarize data on controversial dilemmas in staging procedures, active surveillance and post-chemotherapy assessment of GCTs based on available published literature.